ASSESSMENT OF DRUG RELATED PROBLEMS IN A TERTIARY CARE TEACHING HOSPITAL, INDIA - SARFARAZ MOHAMMED; Poudel, Sanjay; FERNANCE LALOO; ARJUN MADHUR; RINSON ROBERT; Mathew, Binu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Objective: Drug related problems (DRPs) are frequent in hospitalization where multiple changes in patient’s medication regimen and lack of continuity of care may be accompanied. The aim of present research was to identify drug related problems, drug classes involved in DRPs as well as associated factors with the occurrence of DRPs and to assess the pharmacist interventions in a tertiary care teaching hospital. Methods: A prospective observational study was carried out in a tertiary care teaching hospital, over a period of six months from November 2015 to April 2016. All the in patients admitted to all departments of hospital, who satisfied the selection criteria, were included in this study. Necessary demographic and clinical data was collected from the case records. The Pharmaceutical Care Network Europe Classification Version (PCNE) 5.01 was used to classify DRPs. The treatment data was analyzed to determine the rate, pattern, clinical significance, and outcomes of DRPs. Results: A total of 300 patient case sheets were reviewed during the study period, out of which 143 drug related problems were identified from 93 patients. Male (%) predominance was noted over females (%). The most common DRP was drug Interactions 47.55% (68) followed by drug use problems 19.58% (28), drug choice problems 14.68% (21), others 11.88% (17), dosing problems 4.89% (7), and adverse reaction 1.39% (2) were identified. Conclusion: Drug related problems are common among the wards of hospital. Clinical pharmacist’s role in identification, resolution and prevention of drug related problems helps in achieving better therapeutic outcomes and improved patient healthcare. Keywords: DRP’s, Adverse Drug Reactions, Drug Interactions (DI), Drug choice problems, Dosing problem, Drug use problems, Paediatric, Medicine, PCNE